2014
DOI: 10.1177/0363546514552788
|View full text |Cite
|
Sign up to set email alerts
|

Patient Predictors of Early Revision Surgery After Anterior Cruciate Ligament Reconstruction

Abstract: Soccer players and adolescents had an increased risk of revision surgery after ACL reconstruction, with a respective factor of 1.5 and 2.5. Individuals with a combination of these 2 predictors carried an almost 3-fold higher risk of revision surgery. There were no significant associations for sex, height, weight, body mass index, or tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
168
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(183 citation statements)
references
References 28 publications
9
168
3
3
Order By: Relevance
“…Compliance with rehabilitation programmes is substantially lower among younger athletes, which might also contribute to the higher ACL re-injury risk 7. Based on data from the Swedish National Knee Ligament Register, the combination of being young and playing football is a substantial risk factor for revision surgery 13 17…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with rehabilitation programmes is substantially lower among younger athletes, which might also contribute to the higher ACL re-injury risk 7. Based on data from the Swedish National Knee Ligament Register, the combination of being young and playing football is a substantial risk factor for revision surgery 13 17…”
Section: Introductionmentioning
confidence: 99%
“…Whereas 73 % of good objective results and satisfactory subjective results were documented, 57 % of patients did not return to the same level of sport activity, significantly inferior to that of a primary procedure. Although significant advances in ACL reconstructive surgery have been made in the past decade, graft failure continues to occur, with a reported rate of about 2 % of patients in the first 2 years [4] and 11.9 % at 10 years [15]. Several factors can account for reinjuries, including young patient age, high sports activity level, prior meniscectomy, or errors in surgical technique such as improper graft placement, tensioning, fixation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that adolescents may well have a higher risk of ACL graft ruptures, have a higher preoperative activity level, have issues with compliance with rehabilitation, and be more likely to place the graft at risk. 3,26 Our study has not shown ACL graft survival to be significantly lower in adolescents than adults. However, the strongest predictor of contralateral ACL ruptures was age \18 years compared with age .18 years (56% vs 25%, respectively).…”
Section: Agementioning
confidence: 56%